2009
DOI: 10.1021/jp810156j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Elementary Steps in the Reactions between Aluminum and Teflon Fragments under Combustive Environments

Abstract: Gas-phase reactions between aluminum particles and Teflon fragments were studied to develop a fundamental understanding of the decomposition reactions and combustion processes of the Al-Teflon composites. The reactions were investigated theoretically using ab initio calculations at the MP2/aug-cc-pVDZ level, with the final thermokinetic data obtained with coupled cluster theory (CCSD(T)/aug-cc-pVTZ). Among reactions under oxygen-lean conditions, CF 3 + Al f CF 2 + AlF channel is the fastest, followed by the CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…The presence of oxygen in the plasma, even under N 2 environment, caused by working under atmospheric pressure conditions and the layer of oxidized aluminium on the surface, enables reaction channels that lead to the creation of carbonic fluorides (COF x ), through many reactions originating from different fragments of C 4 F 8, which are reviewed in [15] , for example: …”
Section: Resultsmentioning
confidence: 99%
“…The presence of oxygen in the plasma, even under N 2 environment, caused by working under atmospheric pressure conditions and the layer of oxidized aluminium on the surface, enables reaction channels that lead to the creation of carbonic fluorides (COF x ), through many reactions originating from different fragments of C 4 F 8, which are reviewed in [15] , for example: …”
Section: Resultsmentioning
confidence: 99%
“…6 The reaction time in turn is essentially determined by what intermediated reaction products are produced, i.e., the reaction pathways. [6][7][8] It has been suggested that the slow formation time of certain products play an essential role in determining the reaction time of some HEs. 6,9,10 However, the molecular process that determine the reaction time are largely unknown.…”
Section: -3mentioning
confidence: 99%
“…such a reaction system were studied by Losada et. al [3] and serve as the basis for this paper. Let { ji ν } (1≤j ≤S, 1≤i ≤N) be the stoichiometric matrix for the reaction system.…”
Section: Kineticsmentioning
confidence: 99%
“…The system of ordinary differential equations (ODEs) (eqs. 1-3) is computed with the rate data set shown in [3] and the resulting λ profiles of the solution at various initial conditions in the range of temperature up to 4000 K, Figure 1. Note that the temperature of the mixture under reaction decreases significantly at initial reaction period as shown in Figure 1.…”
Section: Kineticsmentioning
confidence: 99%